PRINCIPLES OF SELECTION OF CHILDREN WITH HEARING DEFECTS INTO SPECIAL EDUCATIONAL INSTITUTIONS - Kahramonova Zebuniso Raufjonovna (TADQIQOTLAR, 2026)
Abstract.  This  article  provides  information  on  the  principles  of  selection  of children with hearing impairment to special educational institutions. The practice of special  schools  for  hearing  impaired  children  has  clearly  confirmed  that  teaching children with hearing impairments from different groups together does not produce effective results.